Is secular–religious party competition moving online? Digital religious profiles of candidates running for the European Parliament - Euchner, Eva-Maria; Schweizer, David; Braun, Daniela (Frontiers in Political Science, 2025)
New digital technologies alter various societal spheres, including the landscape of religion and politics. “Christianity influencers,” faith tweets, digital chaplaincy and online Islamic hate speech are notable examples in place. The rapidly growing body of scholarship known as digital religion studies explores the extent to which traditional religious practices are being adapted to digital environments. However, while this nascent field profits from interdisciplinary perspectives, the political dimension of this transformation is still underdeveloped. Specifically, it is unclear how political actors refer to religion during online campaigning across Europe and whether the existing patterns reflect “classical offline divides” between secular and religious parties. This paper contributes to this gap by providing first-hand empirical evidence of online references to religion by candidates running for the European Parliament in 2019 in four countries (Germany, Sweden, the Netherlands and the United Kingdom). The study uses a mixed-methods approach, combining qualitative and quantitative analyses of European politicians’ X (formerly Twitter) profiles. Overall, religion plays a subordinate role in online political campaigning; however, there is substantial country variation, indicating a higher salience of religion in Swedish and Dutch campaigns in comparison to German or British online discourses. Furthermore, candidates from political parties with religious roots are more likely to refer to religion than those from more secular parties, reflecting traditional secular-religious divisions. The paper advances existing research on religion and party politics through its fresh perspective on religion outside classical arenas of political conflict and inside important alternative venues of political competition.